Nereididae (Annelida: Phyllodocida) of Lizard Island, Great Barrier Reef, Australia - Glasby, Christopher J. (Zootaxa, 2015)
Nereididae is one of the most ubiquitous of polychaete families, yet knowledge of their diversity in the northern Great Barrier Reef is poor; few species have been previously reported from any of the atolls or islands including Lizard Island. In this study, the diversity of the family from Lizard Island and surrounding reefs is documented based on museum collections derived from surveys conducted mostly over the last seven years. The Lizard Island nereidid fauna was found to be represented by 14 genera and 38 species/species groups, including 11 putative new species. Twelve species are newly reported from Lizard Island; four of these are also first records for Australia. For each genus and species, diagnoses and/or taxonomic remarks are provided in addition to notes on their habitat on Lizard Island, and general distribution; the existence of tissue samples tied to vouchered museum specimens is indicated. Fluorescence photography is used to help distinguish closely similar species of Nereis and Platynereis. A key is provided to facilitate identification and encourage further taxonomic, molecular and ecological studies on the group.